2015
DOI: 10.1016/j.frl.2015.06.001
|View full text |Cite
|
Sign up to set email alerts
|

The benefits of combining seasonal anomalies and technical trading rules

Abstract: a b s t r a c tAlthough many seasonal anomalies and technical trading rules have been shown to have predictive ability, investigations have focused only on them operating individually. We study the benefits of trading based on combinations of three of the best known effects: the moving average rule, the turn of the month effect, and the Halloween effect. We show that the rules can be combined effectively, giving significant levels of returns predictability with low risk and offering the possibility of profitab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
1
0
1
Order By: Relevance
“…Para el caso Colombiano no se han realizado estudios que analicen de forma adecuada la efectividad de combinar el análisis técnico y el estudio de anomalías en el mercado con el fin de diseñar estrategias de inversión bursátil. Gebka et al (2015), para el mercado estadunidense, investigan el beneficio de combinar indicadores de análisis técnico con el estudio de anomalías del mercado, encontrando que las reglas se pueden combinar efectivamente encontrando niveles significativos de rendimientos.…”
Section: Revisión De Investigaciones Empíricasunclassified
“…Para el caso Colombiano no se han realizado estudios que analicen de forma adecuada la efectividad de combinar el análisis técnico y el estudio de anomalías en el mercado con el fin de diseñar estrategias de inversión bursátil. Gebka et al (2015), para el mercado estadunidense, investigan el beneficio de combinar indicadores de análisis técnico con el estudio de anomalías del mercado, encontrando que las reglas se pueden combinar efectivamente encontrando niveles significativos de rendimientos.…”
Section: Revisión De Investigaciones Empíricasunclassified
“…They concluded that the seasonal patterns were stronger in small-cap shares. Gebka, Hudson and Atanasova (2015) came to conclusion that seasonal anomalies in combination with technical analysis are able to generate significant returns with low risk.…”
Section: Literature Reviewmentioning
confidence: 99%